What does the term file and plenty of proposed Lithuanian substitutes mean? - Zajankauskas, Stasys (Information & Media, 1996)
The article is devoted to search for Lithuanian term suitable to substitute English computer term file. The concept denoted by the English term is disclosed, development of previously used Lithuanian terms is analysed. New term sauginys is proposed on the basis of reveal of the concept. Terms tvarkinys, ruošinys, aplankas, and išstata as substitutions for terms (File), template, directory, and setting/option/set up accordingly are discussed as well.
Keywords: -